Pelatihan Kader Kesehatan Tentang Pengisian KMS Dan Buku KIA Di Desa Blaru Kabupaten Pati - Siti Ni’amah (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background: Monitoring the growth and development of children is very important for early detection of disorders of growth and development of children. Growth monitoring is carried out by weighing and measuring height regularly every month, while developmental assessment can be carried out using a developmental pre-screening questionnaire (KPSP) or MCH handbook. Health cadres play a very important role in filling out the MCH and KMS books to help make the child health program a success. Purpose: Health cadres know how to fill out MCH and KMS Books correctly and are able to practice how to fill MCH and KMS Books correctly. Method: Provide transfer of knowledge to health cadres by conducting counseling about filling out KMS and MCH books and providing training to health cadres in filling out KMS and MCH Handbooks. Results:Health cadres were able to practice how to fill out the MCH and KMS books correctly. Conclusion: after the training for filling out the KIA and KMS books, there was an increase in the skills of health cadres about filling out the KMS and KIA books